2010
DOI: 10.1002/masy.200900105
|View full text |Cite
|
Sign up to set email alerts
|

The Rebinding Properties of Bovine Serum Albumin Imprinted Calcium Alginate/Phosphate Hybrid Microspheres Via the Adjustment of pH Values and Salt Concentration

Abstract: Summary: Bovine serum albumin imprinted calcium phosphate/alginate hydrogel microspheres were prepared with sodium alginate (SA), (NH4)2HPO4, and using CaCl2 as gelling agent, bovine serum albumin (BSA) as template in inverse suspension. The optimized rebinding properties of BSA imprinted hydrogel microspheres were investigated by controlling pH value and ionic concentration from the viewpoint of adjusting the process of gelling, removing template and rebinding. The optimized pH values for the imprinting of BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…and Herrero and coworkers prepared bovine serum albumin (BSA) imprinted calcium alginate (CaA) hydrogel microspheres under mild circumstances. Zhao et al . prepared BSA‐imprinted CaA/phosphate hybrid microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…and Herrero and coworkers prepared bovine serum albumin (BSA) imprinted calcium alginate (CaA) hydrogel microspheres under mild circumstances. Zhao et al . prepared BSA‐imprinted CaA/phosphate hybrid microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Oral et al reported pH-responsive and recognitive polymeric networks based on PEG star polymers to distinguish D-glucose from similar sugars by using methylacryl acid (MAA) as the ionizable comonomer [104]. In addition, equilibrium swelling and rebinding properties of BSA imprinted hybrid hydrogel microspheres based on calcium alginate and phosphate were also evaluated in different pH values and even ionic concentrations [105]. Recently, this type of pH-responsive imprinted hydrogels was applied as horseradish peroxidase mimetic enzymes.…”
Section: Ph-responsive Molecularly Imprinted Polymersmentioning
confidence: 99%
“…imprinted hybrid hydrogel microspheres based on calcium alginate and phosphate were also evaluated in different pH values and even ionic concentrations [105]. Recently, this type of pH-responsive imprinted hydrogels was applied as horseradish peroxidase mimetic enzymes.…”
Section: Ph-responsive Molecularly Imprinted Polymersmentioning
confidence: 99%